Effectiveness of the Implementation of the Law on Sexual Violence Crimes and Government Regulation Number 30 of 2025 on Legal Protection for Child Victims of Sexual Violence - Purba, Dhea Aulia Malem; Kalingga, Qori Rizqiah H; Tarigan, Evi Yunita (Civiliza Publishing, 2025)
Children are legal subjects who have the right to protection from all forms of violence, including sexual violence. The state is obliged to guarantee this protection through the formation and implementation of laws and regulations oriented towards the best interests of children. Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence (TPKS Law), which is reinforced by Government Regulation Number 30 of 2025 as an implementing regulation, is present to provide comprehensive legal protection for child victims of sexual violence. This regulation comprehensively regulates the rights of victims, including procedural rights in the judicial process, the right to protection from degrading or blaming treatment, and the right to recovery through medical, psychological, and social rehabilitation, social empowerment, and the fulfillment of economic rights in the form of restitution, compensation, and victim assistance funds. This study aims to analyze the forms of legal protection for child victims of sexual violence from the perspective of the TPKS Law and Government Regulation Number 30 of 2025. The research method used is normative legal research with a legislative and conceptual approach. The research results show that although the regulatory framework is adequately available, its implementation still faces various challenges, particularly related to the low level of understanding of the authorities and the public regarding the victim's perspective.